2005
DOI: 10.1097/01.cad.0000180122.24031.13
|View full text |Cite
|
Sign up to set email alerts
|

Lasting remission following multimodal treatment in a patient with metastatic breast cancer

Abstract: We report on a lasting remission from multimodal treatment in a patient with hepatic metastasized breast cancer. After surgical removal of a singular hepatic metastasis, the patient underwent leukapheresis of peripheral blood mononuclear cell (PBMCs). For induction chemotherapy, the patient received 2 cycles of epirubicin and paclitaxel (ET). After 1 cycle of epirubicin and ifosfamide (EI), peripheral blood stem cells were harvested. After a final cycle of ET, the patient underwent high-dose chemotherapy (HDCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Indeed, intraperitoneal treatment with an EpCAMtargeted trAb in patients with malignant ascites resulted in the complete elimination of tumor cells in ascites as well as disappearance of ascites accumulation (35). Moreover, a recent pilot study has demonstrated the feasibility using trifunctional antibodies with anti-EpCAM X anti-CD3 and anti-Her2 X anti-CD3 in combination with high-dose chemotherapy and autologous stem cell transplantation in metastatic breast carcinoma (36). Patients treated with the trAbs showed a trend towards improved overall survival.…”
Section: Trifunctional Bispecific Antibodies For Epcampositive Carcinomamentioning
confidence: 99%
“…Indeed, intraperitoneal treatment with an EpCAMtargeted trAb in patients with malignant ascites resulted in the complete elimination of tumor cells in ascites as well as disappearance of ascites accumulation (35). Moreover, a recent pilot study has demonstrated the feasibility using trifunctional antibodies with anti-EpCAM X anti-CD3 and anti-Her2 X anti-CD3 in combination with high-dose chemotherapy and autologous stem cell transplantation in metastatic breast carcinoma (36). Patients treated with the trAbs showed a trend towards improved overall survival.…”
Section: Trifunctional Bispecific Antibodies For Epcampositive Carcinomamentioning
confidence: 99%